Thinking About Thinking in Physics: A Systematic Review on Metacognitive Approaches for Secondary Students - Kurniaty, Dewi; Muslim, Muslim; Novia, Hera (Jurnal Pendidikan MIPA, 2025)
This review examines the literature on metacognitive strategies implemented in high school physics from 2021 to 2025, using Schraw's control framework, which encompasses planning, monitoring, and evaluation. The goal is to identify structural weaknesses that hinder overall theoretical progress and practical application in the classroom. Using PRISMA principles, an article search in ERIC yielded 244 documents, 22 of which were Scopus-indexed studies that met the criteria. We outline study designs, evaluation instruments, types of interventions, participants, and study objectives. A thematic synthesis addressed three guiding questions: (1) which instructional strategies contribute to metacognitive growth, (2) which evaluative instruments were used, and (3) what implementation conditions and challenges exist. Four main intervention categories were identified. Cognitive-reflective strategies foster self-awareness and introspection. Various inquiry methods combine metacognitive control with scientific investigation. Tools that aid visualization and representation of concepts, particularly simulations and concept maps, are key to organizing and maintaining coherent information. Gender-sensitive sociocultural and affective strategies foster motivation and inclusivity. All studies reported that these interventions had positive impacts on problem-solving, self-efficacy, and conceptual understanding. However, based on Schraw's hypothesis, this review identified planning as the most underdeveloped and neglected aspect of metacognitive regulation. Most studies relied heavily on self-reporting, leaving limited opportunities for task-embedded or multimodal assessments. Most designs were quasi-experimental or survey-based, and very few included mixed-methods or technology-mediated assessments. This research suggests combining structured insights, including goal setting, preemptive questioning, and activity design, with authentic assessments such as portfolios and think-aloud rubrics. Using these approaches within an equity-centered and culturally responsive pedagogy can foster active and self-directed learning in physics. Future research should aim to expand planning elements, diversify assessment techniques, and use educational technology to enhance and simplify metacognitive instruction in instructional design.    Keywords: metacognition, physics education, high school students, systematic literature review, thinking awareness.